Agency via Life Satisfaction as a Protective Factor From Cumulative Trauma and Emotional Distress Among Bedouin Children in Palestine - Veronese, Guido; Pepe, Alessandro; Cavazzoni, Federica; Obaid, Hania; Perez, Jesus (Frontiers in Psychology, 2019)
Adopting an ecological perspective on children’s functioning and psychological well-being, we investigated the association between agency and life satisfaction, and its bearing on trauma symptoms and negative emotions in a group of Bedouin children living in the occupied Palestinian territories. Specifically, we hypothesized that the more children were agentic, the more they would be satisfied with their lives; and that greater life satisfaction would be associated with reduced trauma symptoms. A sample of 286 Bedouin children attending primary schools in four different villages in the Jordan Valley completed the Multidimensional Students’ Life Satisfaction Scale (MSLSS), Positive Affect and Negative Affect Scale for Children (PANAS-C), Children’s Impact of Event Scale (CRIES-13), and the Children’s Hope Scale (CHS). Structural equation modelling was performed to evaluate the cumulative network of direct and indirect effects between children’s agency, life satisfaction, and trauma symptoms. The findings confirmed the key role of life satisfaction in mitigating traumatic reactions. Higher levels of life satisfaction were associated with reduced negative emotions and trauma symptoms, suggesting that agency may be viewed as a pre-determining factor with the potential to protect children from trauma symptoms. We discuss the implications for research and clinical practice.